The Effect of Blended Learning Model (BLM) on Student Achievements: A Meta-Analysis - Asrizal Asrizal; Ukhlufi Khairi; Yulkifli; Murtiani Murtiani; Vivi Mardian (Postgraduate, University of Mataram, 2022)
The 21st-century learning requires teachers to develop the abilities of students and change the learning system from teacher-centered to student-centered. In fact, the learning process still uses conventional and teacher-centered methods, so that student learning outcomes are low. For this reason, the BLM (Blended Learning Model) is applied to improve student learning outcomes in physics subjects. This study aims to determine the effect of similar studies using the BLM on students’ achievement. The type of research used is meta-analysis research with a quantitative approach. The results of this study are the first, namely the influence of similar studies from the BLM which shows that BLM has a significant influence on student achievement. Second, based on grade level, the effect of similar studies from the BLM shows that grade XI has a more significant impact. Third, based on the learning material, the effect of similar studies from the BLM shows that the optical topic has a significant impact. Fourth, based on learning media that has a more significant impact than similar studies, namely the schoology application. This research can be used as a reference for developing BLM on different materials, school levels, and various interactive media